A multi-level modeling approach to guide management of female feral hogs in Great Smoky Mountains National Park - Frances E. Buderman; Patrick J. Helm; Joseph D. Clark; Ryan H. Williamson; Joseph Yarkovich; Jennifer M. Mullinax (Biological Invasions, 2023)
We trapped, anesthetized, and fit 16 female feral swine ( Sus scrofa ) with Global Positioning System (GPS) collars in Great Smoky Mountains National Park (GRSM) to develop predictive summer and winter models for more effective population control efforts. Given the highly diverse habitat and topography in GRSM and the spatial extent of our dataset, we employed Step Selection Function (SSF) to evaluate resource selection at the 3 rd -order level and Resource Selection Function (RSF) models at the 2 nd -order level for both summer and winter seasons. The summer SSF and RSF models suggested relatively similar levels of selection, whereas the winter models differed by method. We created a straightforward consensus model to better visualize the agreement and constraints of each set of models. In summer, feral swine used lower slopes regardless of elevation, especially those closer to human-dominated spaces such as along paved and gravel roadways. In winter, feral swine maintained preference for lower slopes but preferred oak-dominated forest areas and selection for human development was less than in summer. Wildlife managers can use these models to better focus feral swine surveillance and management in GRSM. Managers can identify areas of high use by season and plan control activities that are both accessible and highly efficient. The combination and consensus framework presented here can be applied to other systems where species’ habitat selection may result in incongruous results across different levels of selection or seasons of interest.